A Study on the Pragmatic Functions of Emojis in Chinese Consumers’ Digital Reviews - Liang, Li (Sinología hispánica. China Studies Review, 2026)
Emojis, as a widely used multimodal resource in computer-mediated communication (CMC), have attracted considerable academic interest in recent years. However, most pragmatic studies on emojis have focused on discourse genres such as online chat and social media discourse, while research on their use in online consumer reviews remains relatively scarce. The present study aims to explore the pragmatic functions of emojis in consumer reviews and their application in this domain based on the analysis of 450 reviews collected from the Chinese review websites Dianping.com. The findings reveal that the functional distribution of emojis in consumer reviews is generally consistent with that observed in other digital discourse genres, though certain differences are also evident, primarily reflected in their decorative function. Furthermore, Chinese consumers tend to use emojis with features specific to the Chinese digital context to convey a wide range of pragmatic functions.